2018
DOI: 10.1134/s0006297918020013
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Yeast Mitochondrial Translation: Who Is in Charge?

Abstract: Mitochondrial genome has undergone significant reduction in a course of evolution; however, it still contains a set of protein-encoding genes and requires translational machinery for their expression. Mitochondrial translation is of the prokaryotic type with several remarkable differences. This review is dedicated to one of the most puzzling features of mitochondrial protein synthesis, namely, the system of translational activators, i.e., proteins that specifically regulate translation of individual mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 97 publications
0
20
0
Order By: Relevance
“…S5 E and G). This pattern can be justified by the fact that the core subunits of the respiratory-chain complexes are synthesized locally by mitochondrial ribosomes (48). Otherwise, we observed that some functional protein groups (Heme biosynthesis and proteins involved in the mitochondrial genome maintenance; SI Appendix, Fig.…”
Section: Mitochondrial Absolute Proteome Allocation and Variation Of Thementioning
confidence: 83%
“…S5 E and G). This pattern can be justified by the fact that the core subunits of the respiratory-chain complexes are synthesized locally by mitochondrial ribosomes (48). Otherwise, we observed that some functional protein groups (Heme biosynthesis and proteins involved in the mitochondrial genome maintenance; SI Appendix, Fig.…”
Section: Mitochondrial Absolute Proteome Allocation and Variation Of Thementioning
confidence: 83%
“…Therefore, accordingly to the data presented here, we hypothesized that in the absence of formylated methionyl‐tRNA, Msc6p is required for proper expression of mitochondrially encoded products. Different studies on mitochondrial translation have unveiled a multitude of factors involved in this process , particularly Cox1p whose translation involves a number of regulatory steps from mRNA processing to the newly synthesized stabilization .…”
Section: Discussionmentioning
confidence: 99%
“…The dependence on two separated genomes for proper assembly of the respiratory complexes required the development of a balanced output of gene products destined to be subunits of the same enzyme. Mitochondria translational activators are the primary candidates to exert such control (Costanzo and Fox, 1990) in three proposed ways: through the recognition of a specific 5' UTR end, which is the case of Cbp1p, Cbs1p and Cbs2p; by a direct interaction with the mitoribosome (Cbs1p, Cbs2p, Cbp3p and Cbp6p); and finally interacting with the nascent polypeptide chain at the mitoribosome tunnel exit (Cbp3p and Cbp6p) (Derbikova et al, 2018;Ndi et al, 2018).…”
Section: -Mitochondrial Gene Expressionmentioning
confidence: 99%